Parents at school: one more result from the function psychoanalysis and education - Fragelli, Ilana Katz Zagury (Clinical Styles. The Journal on the vicissitudes of childhood, 1998)
This paper aims to discuss about the possibilities of intervention in the assistence to parents in an institution for education using references brought up through the confluence of psychoanalyses and education.